Tracking the path of predator recognition in a predator-naive population of the pond snail. (28th December 2022) - Batabyal, Anuradha; Lukowiak, Ken
Abstract: Organisms evolve adaptive strategies to adjust to rapidly changing environmental stressors. Predation pressure is one of the strongest selective forces and organisms respond to predatory threats via innate and learned responses. We utilized a natural, experimental set-up, where two lakes Stoney and Margo in Canada containing natural populations of the prey Lymnaea stagnalis differed in the presence and absence of an invasive, predatory Northern crayfish, Faxonius virilis. We exploited the contrast in the predation backgrounds of the snail populations from the two lakes to test, 1) predator recognition in predator - experienced snails is innate, (2) predator - naive snails learn to detect a novel invasive predator, and 3) learning about a novel predator gets transmitted to the successive generations. We quantified predator fear memory formation using a higher-order learning paradigm called configural learning. We found that 1) predator recognition in predator-experienced snails is innate, 2) predator-naive snails learned to recognize the novel predator even after a brief exposure to predator cues highlighting the role of learning in combating invasive predators and the critical time-window during development that accounts for predator recognition, and 3) the learning and predator detection mechanism in predator-naive snails are not transmitted to successive generations. The population variation observed in the predator-detection mechanism may be due to the past and current experience of predators in one population over the other. We find an interesting study system to address how fear learning occurs and prospective future directions to understand the mechanism of innate fear recognition from a learned fear recognition. Abstract : Ecosystems are invaded by novel exotic predators that pose a severe threat to the native prey population. The optimal strategy for prey is to learn and form a memory of the novel threat. We show that prey animals can learn about novel predators when exposed to predator cues during a critical developmental period. However, this learned predator recognition is not passed on from the parents to the offspring.